Efektivitas Penerapan Sistem Aplikasi Pelayanan Kepegawain (SAPK) Terhadap Pelayanan Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Aceh Singkil - Marzufri, Ahmad; handayani, Sriwahyu (Universitas Muhammadiyah Mataram, 2022)
Developing a Personnel Service Application System (SAPK) as a form of embodiment of the implementation of e-government for users of information and communication technology in government, In this case the SAPK aims to realize up-to-date staffing data that is transparent and objective at every level of the agency from the central to the regional that is integrated in an integrated manner. national. This research was conducted at the Agency for Personnel and Human Resources Development (BKPSDM) Aceh Singkil, in this study the approach used was a qualitative approach using descriptive analysis, where to obtain data using interview, observation, and documentation techniques, Application of the Personnel Service Application System ( SAPK) this form of service is very easy to help, both in proposing services letters, as well as in searching for the required data, the difference is clear before the application of the SAPK application, manual file searches used to still use correspondence and archival paper, the Personnel Application System (SAPK) which has been used in the Agency for Personnel and Human Resources Development (BKPSDM) Aceh Singkil in its application has been effective, it's just that the lack of achievement is in the facilities and infrastructure section which is still lacking, while in other types of correspondence it is still done manually.